The influence of problem-based learning with socio-scientific issues on improving concept mastery and critical thinking in biotechnology - Devi Nurfadhila; Diana Vivanti Sigit; Tri Handayani Kurniati (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2026)
The low conceptual mastery and critical thinking skills of grade 10 students in biotechnology create a need for a more contextual and meaningful learning model. This study aims to determine the effect of the Problem Based Learning (PBL) model integrated with Socio-Scientific Issues (SSI) on conceptual mastery and critical thinking skills in biotechnology. The study used a quasi-experimental design with two groups: an experimental class using PBL integrated with SSI and a control class using the Discovery Learning model. Data were collected through pre-tests and post-tests using multiple-choice questions for conceptual mastery and essays for critical thinking skills. The research results show that the experimental class had an average conceptual mastery score of 85, which was higher than the control class’s score of 67. For critical thinking skills, the experimental class obtained an average score of 81, while the control class scored 74. The MANOVA statistical test yielded p < 0.05, indicating that the PBL-SSI model had a significant effect on conceptual mastery and critical thinking skills. N-Gain analysis showed a high increase in the experimental group and a moderate increase in the control group. This indicates that integrating PBL with SSI creates a meaningful learning environment, promoting better conceptual understanding and critical thinking skills. The impact of this study is expected to serve as a reference for developing innovative learning methods in future biology education.Abstrak. Keterampilan penguasaan konsep dan berpikir kritis siswa kelas 10 dalam bioteknologi yang rendah menciptakan kebutuhan akan model pembelajaran yang lebih kontekstual dan bermakna. Penelitian ini bertujuan untuk menentukan pengaruh model Pembelajaran Berbasis Masalah (PBL) yang terintegrasi dengan Isu-Isu Sosial-Ilmiah (SSI) terhadap penguasaan konsep dan keterampilan berpikir kritis dalam bioteknologi. Penelitian ini menggunakan desain quasi-eksperimental dengan dua kelompok: kelas eksperimen yang menggunakan PBL terintegrasi dengan SSI dan kelas kontrol yang menggunakan model Pembelajaran Penemuan. Data dikumpulkan melalui tes awal dan tes akhir menggunakan soal pilihan ganda untuk penguasaan konsep dan esai untuk keterampilan berpikir kritis. Hasil penelitian menunjukkan bahwa kelas eksperimen memiliki skor rata-rata penguasaan konsep sebesar 85, yang lebih tinggi daripada skor kelas kontrol sebesar 67. Untuk keterampilan berpikir kritis, kelas eksperimen memperoleh skor rata-rata 81, sementara kelas kontrol mendapatkan skor 74. Uji statistik MANOVA menghasilkan p < 0.05, menunjukkan bahwa model PBL-SSI memiliki dampak signifikan terhadap penguasaan konsep dan keterampilan berpikir kritis. Analisis N-Gain menunjukkan peningkatan tinggi pada kelompok eksperimen dan peningkatan moderat pada kelompok kontrol. Hal ini menunjukkan bahwa integrasi PBL dengan SSI menciptakan lingkungan belajar yang bermakna, yang mempromosikan pemahaman konseptual yang lebih baik dan keterampilan berpikir kritis. Dampak penelitian ini diharapkan dapat menjadi acuan untuk mengembangkan metode pembelajaran inovatif dalam pendidikan biologi di masa depan.